Pengaruh Partisipasi Penyusunan Anggaran, Gaya Kepemimpinan Dan Good Governance Terhadap Kinerja Pemerintahan Desa Panggungrejo Kecamatan Kauman Kabupaten Tulungagung - Ferdy Bagas Cahyono; Amin Tohari; Sugeng Sugeng (Universitas 17 Agustus 1945, 2023)
This research aims to analyze the influence of participation in budget preparation, leadership style, and good governance on the performance of the Panggungrejo Village government, Kauman District, Tulungagung Regency. This research uses a quantitative approach, with a casual research technique. Data collection was carried out using a questionnaire. The population and sample were all village officials at the Panggungrejo Village Office and analyzed using multiple linear regression with SPSS software. Researchers used statistical tests (F test) and partial tests (t test). The results of the F test show a significance figure of 0.000 < 0.005, which means that these three variables have a significant effect on the performance of the village government. The results of the partial test (t) show a significance figure of 0.004 < sig. 0.05 on X1 which means there is an influence of budget participation on the performance of the village government, 0.364 < 0.05 on It can be concluded that budget preparation and good governance have a significant influence on village government performance, while leadership style does not have a significant influence on village government performance. So, if these variables increase, government performance will also increase.